Blockchain Technology Meets Traceability in Fruit Supply Chain Management: A Systematic Review - Resista Vikaliana; Raja Zuraidah Raja Mohd Ras; I Nyoman Pujawan; Irwansyah (IPB University, 2021)
Fruits are easily damaged, therefore, a tracing system is needed to ensure the commodity is well received by consumers. This study is a systematic review aims to identify areas where the fruits traceability provides the most value for supply chain management and to develop elements of a future research agenda for the fruits traceability in supply chain management. PRISMA or Preferred Reporting Items for Systematic Reviews and Meta-Analyses is used to help the systematic literature review. The result showed thad there are several values ​​in applying traceability to the fruit supply chain, such as traceability guarantees the quality of fruit in the supply chain, traceability protects from fraud. Traceability will help increase consumer confidence in food safety, particularly on fruit. Blockchain technology is a promosing technology for a traceability system in industry and can be used successfully, by modifying the supply chain system and meeting the limitations first.